Synthesis and preliminary antimicrobial evaluation of new 7-amino-4-methyl-coumarin thiazolidinone conjugates - Muthanna S. Farhan; Tuka Hassan Abd-Elhussain; Azhar Mahdi Jasim (Pensoft Publishers, 2024)
As a part of our ongoing project on the design and synthesis of new 4-thiazolidinone derivatives with antimicrobial activity, four new 4-thiazolidinone derivatives carrying bromo, nitro, methyl, and chloro groups on the benzene ring were synthesized by starting with the 7-amino-4-methylcoumarin moiety, linking coumarin with various phenyl isothiocynate to form the thiourea group, and then cyclizing the derivatives, characterized by IR and 1HNMR, and assayed in vitro for their antimicrobial activity against Gram positive and Gram negative bacteria and fungi. Overall, 2-(4-methyl-2-oxo-2H-chromen-3-yl)-3-(4-nitrophenyl) thiazolidin-4-one to be the most powerful individuals in the series. Based on the observed data, it can be stated that the synthesized compounds demonstrate a variable range of antibacterial activity.